Katechizm narzędziem katechezy – bogactwo tradycji wobec wyzwań współczesności - Osial, Wojciech (Collectanea Theologica, 2018)
The article is an attempt to show the most important questions concerning the use of catechism in contemporary catechesis. Special attention is focused on the necessity of catechism in religious education, but the author also describes the difficulties related to the teaching of this catechism. This theme is first analyzed in the light of history and catechetical documents. The first part of the reflection is a historical review of catechism contained in catechesis. In the second part the author analyzes the most important documents for catechesis and searches in them contents about the problem of catechism in catechesis: the General Catechetical Directory of 1971, the Apostolic Exhortation Catechesi tradendae of 1979, the General Directory for Catechesis of 1997 and the Directory for Catechesis of the Catholic Church in Poland of 2001. In the third part one finds the analyses of the most important problems concerning the use of catechism in the practice of catechesis. The following challenges of the new evangelization are pointed out: a crisis of the faith and a problem concerning the knowledge of Christian doctrine, tension between the knowledge of faith and the attitude of faith, and refusal to memorize the catechism formulas.